Fundamental of entrepreneurship (ENT300) : Zumba and Yoga Gumeezum Fitness Centre / Cavin Melvin Moenten ... [et al.] - Moenten, Cavin Melvin; Adenan, Yusuf; Ludi, Nurul Farinna; Ameran, Nurul Sherra Sazreen; Maurice, Danny (2014)
The name of the company that we agreed to choose IS Zumba and Yoga Gumeezum Fitness Centre. The business is in form of partnerships, which consists of five members. Each partner contributes certain amount of cash as agreed in partnership agreement. The main activities for the business is to change customer perception toward exercise, keep people interest with variety of fitness techniques, to challenge and stimulate their mind and body. Furthermore we also want our customer to feeling good and happy either physically or spiritually and we want to increase the likelihood people that will continue exercise to maintain their fitness. For the nature of the business, we would like to provide customers with positive recreation, fitness and wellness programs and better service to the customer.